Energy Fluctuation of Ideal Fermi Gas Trapped under Generic Power Law Potential U=∑i=1dci|xi/ai|ni in d Dimensions. (1st April 2016) - Faruk, Mir Mehedi; Rahman, Md. Muktadir; Debnath, Dwaipayan; Himel, Md. Sakhawat Hossain
Abstract: Energy fluctuation of ideal Fermi gas trapped under generic power law potential U = ∑ i = 1 d c i | x i / a i | n i has been calculated in arbitrary dimensions. Energy fluctuation is scrutinized further in the degenerate limit μ ≫ KB T with the help of Sommerfeld expansion. The dependence of energy fluctuation on dimensionality and power law potential is studied in detail. Most importantly our general result can not only exactly reproduce the recently published result regarding free and harmonically trapped ideal Fermi gas in d = 3 but also can describe the outcome for any power law potential in arbitrary dimension.